Application of an aerosol deposition model to whole body dermal exposure scenarios involving VX. (February 2023) - Bergmann, C.; Bodurtha, P.; Lecavalier, B.; Naqvi, S.; Duncan, S.
Abstract: In this report we present the application of a modified aerosol deposition model to a number of scenarios involving a whole body dermal exposure to the toxic chemical nerve agent VX in the form of a liquid aerosol. An aerosol deposition model is modified to simulate the distribution of deposited aerosolized particles on the surface of a mannequin exposed to a turbulent air stream with a specified aerosol concentration and particle size distribution, using as few turbulence flow parameters as possible. The aerosol deposition model allows for the calculation of deposition velocity, total deposited mass, and other quantities, over the entire surface of a mannequin given the aerosol concentration, exposure time, particle size distribution, and air flow conditions are specified. The model uses shear velocity distributions over a mannequin, obtained from computational fluid dynamic (CFD) simulations, and accounts for three particle transport mechanisms: Brownian (molecular) diffusion, turbulence (eddy) diffusion, and gravitational sedimentation. Additionally, the model considers surface roughness and orientation of the mannequin surface relative to gravity. The model is integrated into a broader computer program, written in the Fortran programming language, that handles all input and output. Highlights: Aerosol deposition model modified for human mannequin at various air velocities. Model considers arbitrary surface geometry and surface roughness. Driven using data from computational fluid dynamics and validated experimentally. Deposition velocity distribution over human mannequin surface. Nerve agent VX dermal exposure hazard analysis using total deposition.